PERAN SHALAT DHUHA SEBAGAI MEKANISME PENGENDALIAN EMOSI PADA MAHASISWA - Annisa Dinda Zaytuna; Agus Abdul Rahman; Hajir Tajiri (MUHAFADZAH: Jurnal Ilmiah Bimbingan dan Konseling Islam, 2026)
College students often face high academic pressure that triggers negative emotions and anxiety, necessitating effective emotion regulation strategies, including spiritual approaches. This study aims to analyze the implementation of dhuha prayer as an emotion control mechanism among college students using a qualitative method with a phenomenological design. Data were collected through in-depth interviews with three students who routinely perform Dhuha prayer using a purposive sampling technique. The results show that Dhuha prayer functions as an antecedent-focused emotion regulation strategy through the process of cognitive reappraisal and a displacement mechanism (redirecting negative energy into positive activities). Significantly, the research subjects experienced behavioral changes ranging from procrastination to productivity, transforming insecurity into self-confidence, and turning the burden of parental expectations into tawakkal (trust in God) motivation. This study concludes that Dhuha prayer is effective as a medium for emotion regulation, capable of providing a relaxation effect, refreshing the mind, and calming the hearts of students amidst academic pressure. Therefore, this practice is recommended as a prevention and intervention strategy in spiritual counseling services for students..